2007
DOI: 10.1007/s00125-007-0870-2
|View full text |Cite
|
Sign up to set email alerts
|

Intensive insulin therapy improves endothelial function and microvascular reactivity in young people with type 1 diabetes

Abstract: Aims/hypothesis Macrovascular disease is an important cause of the increased morbidity and mortality rates associated with type 1 diabetes, and this vascular impairment begins in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…Increased serum levels of sE-selectin have been reported in several connective tissue diseases [4], coronary heart disease [5] and systemic inflammatory response syndrome [6]. Moreover, it has been suggested that sE-selectin plays an important role in the pathogenesis of microvasculature disorders in diabetes [7]. A previous study demonstrated a relationship between sE-selectin serum concentration and microvascular abnormalities in nailfold capillaroscopy in patients with systemic lupus erythematosus (SLE) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Increased serum levels of sE-selectin have been reported in several connective tissue diseases [4], coronary heart disease [5] and systemic inflammatory response syndrome [6]. Moreover, it has been suggested that sE-selectin plays an important role in the pathogenesis of microvasculature disorders in diabetes [7]. A previous study demonstrated a relationship between sE-selectin serum concentration and microvascular abnormalities in nailfold capillaroscopy in patients with systemic lupus erythematosus (SLE) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, extended follow-up of the trial with the biggest between-group difference in insulin use until now (the United Kingdom Prospective Diabetes Study [UKPDS]) revealed a 15% reduction in myocardial infarction and a 13% reduction in death among people with new-onset type 2 diabetes. 15 The UKPDS findings and the potential cardioprotective effects of insulin [16][17][18] suggest that early provision of sufficient basal insulin to normalize fasting plasma glucose levels may safely reduce incident cardiovascular outcomes. Evidence that exogenous insulin may slow the decline in pancreatic function with time [19][20][21] suggests that such an intervention may also reduce incident diabetes in people at risk for the disease.…”
mentioning
confidence: 99%
“…Среди наиболее перспективных следует выделить изучение микроциркуляции в рамках ранней диагностики СД и его осложнений, уточнения риска развития осложнений, мониторинга эффективности ле-чения [35,36,37].…”
Section: применение лдф для оценки микроциркуляции у пациентов с сдunclassified